2004
DOI: 10.1021/jm031067a
|View full text |Cite
|
Sign up to set email alerts
|

Anti-HIV Activity and Conformational Studies of Peptides Derived from the C-Terminal Sequence of SDF-1

Abstract: The entry of the human immunodeficiency virus type 1 (HIV-1) into target cells requires the interaction of viral envelope glycoprotein, gp120, with the human CD4 glycoprotein and a chemokine receptor, usually CCR5 or CXCR4. The natural ligand for CXCR4 is the chemokine SDF-1 that inhibits entry and replication of X4 HIV-1 strains. SDF-1 is produced in two forms, SDF-1alpha (68 residues) and SDF-1beta (72 residues); the difference between them lies in the additional four C-terminal amino acids in the SDF-1beta … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 25 publications
0
11
0
Order By: Relevance
“…CXCL12 has two major isoforms, α and β [16]. Both are derived from a single gene, while CXCL12β differs by an additional four amino acids (RLKM) at the C-terminal end due to alternative splicing [17]. CXCL12α is the predominant isoform secreted by marrow stromal cells and endothelial cells and is found in nearly all organs.…”
Section: Cxcl12 Cxcr4 and Cxcr7mentioning
confidence: 99%
“…CXCL12 has two major isoforms, α and β [16]. Both are derived from a single gene, while CXCL12β differs by an additional four amino acids (RLKM) at the C-terminal end due to alternative splicing [17]. CXCL12α is the predominant isoform secreted by marrow stromal cells and endothelial cells and is found in nearly all organs.…”
Section: Cxcl12 Cxcr4 and Cxcr7mentioning
confidence: 99%
“…22 While the N-terminal sequence of SDF-1 is required for receptor binding, the C-terminal sequence of SDF-1 may affect the binding affinity to the CXCR4 receptor. 51 The absence of the C-terminal lysine in SDF-1 (1-67) may explain its reduced ability to inhibit HIV-1 replication, as we have already shown that SDF-1 (1-67) has reduced binding affinity to heparin/ heparin sulfate glycosaminoglycans as compared with SDF-1 (1-68). 25 In addition to being cleaved at the C-terminus by CPN, SDF-1␣ is cleaved at the N-terminus by a number of different enzymes to generate an inactive chemokine that can no longer activate the CXCR4 receptor, including CD26/dipeptidyl peptidase, 22,26 MMPs, 29 neutrophil elastase, 28 and cathepsin G. 27 The C-terminal loss of lysine is very rapid as compared with a much slower removal of the N-terminal amino acids lysine and proline.…”
Section: Discussionmentioning
confidence: 97%
“…The antibody may recognize an epitope in the C-terminal of SDF-1a, because it did not cross-react with SDF-1b [15]. The difference between SDF-1a (68 residues) and SDF-1b (72 residues) lies in the additional four C-terminal amino acids in the SDF-1b sequence [16].…”
Section: Discussionmentioning
confidence: 99%